Sri Lanka : 2007 Article IV Consultation; Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Alternate Executive Director for Sri Lanka. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2007 Article IV Consultation on Sri Lanka highlights economic growth development and performance. Rising inflation, a high current account deficit, and low unemployment rate indicate that the economy may be operating at full capacity. High stock of public debt, rising near-term debt service needs, and a low level of reserves point to elevated external vulnerabilities. A more determined fiscal consolidation is essential for demand management and debt sustainability. Greater flexibility in the exchange rate is essential to safeguard reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet